Covid-19, trabalho imigrante e o setor dos cuidados: Políticas e Futuro. - Dias, N. (XI Congresso Português de Sociologia, 2021)
During the recent lockdown a sense of community and cohesion arose around certain ideas, such as universal health care, and the aim of specific public policies reinforcing the exceptional circumstances: the immediate regularization of all migrants with processes awaiting decision, prohibition of housing evictions, a lay-off scheme preventing escalation of unemployment, extension of social benefits to vulnerable and precarious occupations, etc. Although the notion of essential workers was largely debated, there was short coverage on how the pandemic affected particular social groups and occupations. And some workers, whose jobs remained essential, were not acknowledged for their endurance during lockdown and beyond. Gradually, some evidences have been emerging regarding the particular impact of Covid-19 on women and, in particular, women in low skilled sectors such as cleaning and caring. Given the furtherance of the recommendation to stay at home, work from home and to avoid public gatherings a significant number of essential jobs are not given the benefit of choice, having had to opt between safety or income. Regarding the care economy, since the year 2000, the official data show some tendencies that are not specific to Portugal. The number of people paying contributions to social security in the category of ‘domestic workers’, meaning they perform a broad range of activities inside personal households, mainly cleaning and caring for infants and elder people, has sharply declined while, at the same time, the percentage of foreign nationalities in the same category has consistently increased. This trend reflects what some authors call an ‘international division of reproductive labor’ that became noticeable in the last decades and a deregulated growth of ‘global care chains’. Migrants are overrepresented in the caring and cleaning sectors in a significant number of countries in the world and allowed families more flexible arrangements regarding the needs of dependent family members. Drawing from official data and in-depth interviews with female migrants working as carers, this paper aims to map the long-run dynamics of the care economy and its relation with recent impacts of covid-19 on the care sector trying to understand the possible outcomes for the sector and for families.